Golden son - Brown, Pierce, 1988- (Brown, Pierce, 1988- Red rising saga, 2015)
"With shades of The Hunger Games, Ender's Game, and Game of Thrones, debut author Pierce Brown's genre-defying epic Red Rising hit the ground running and wasted no time becoming a sensation. Golden Son continues the stunning saga of Darrow, a rebel forged by tragedy, battling to lead his oppressed people to freedom from the overlords of a brutal elitist future built on lies. Now fully embedded among the Gold ruling class, Darrow continues his work to bring down Society from within. A life-or-death tale of vengeance with an unforgettable hero at its heart, Golden Son guarantees Pierce Brown's continuing status as one of fiction's most exciting new voices. Praise for Red Rising "[A] spectacular adventure. one heart-pounding ride. Pierce Brown's dizzyingly good debut novel evokes The Hunger Games, Lord of the Flies, and Ender's Game. [Red Rising] has everything it needs to become meteoric."--Entertainment Weekly "I don't know what Pierce Brown did before he started writing books, but whatever it was, he was wasting his time. Fast-paced, gripping, well-written--the sort of book you cannot put down. I am already on the lookout for the next one."--Terry Brooks, New York Times bestselling author of The Sword of Shannara "Pierce Brown has done an astounding job at delivering a powerful piece of literature that will definitely make a mark in the minds of readers."--The Huffington Post "Ender, Katniss, and now Darrow: Pierce Brown's empire-crushing debut is a sprawling vision of humanity's diaspora to the stars."--Scott Sigler, New York Times bestselling author of Nocturnal "[A] great debut. The author gathers a spread of elements together in much the same way George R. R. Martin does."--Tor.com"--